Dynamite Hollywood exhibition display (circa 1950) - Hercules Incorporated (1950)
General view of an exhibition display advertising the Hercules Powder Company. The individuals visible in the photograph are unidentified. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Hercules Powder Company; Corporations; Chemical industry; Advertising; Advertising, Industrial; Trade shows; Explosives industry